Esther Kobel, Dining with John: Communal Meals and Identity Formation in the Fourth Gospel and its Historical and Cultural Context (Biblical Interpretation Series 109; Leiden – Boston: Brill 2011) - Kręcidło, Janusz (The Biblical Annals, 2016)
Book review: Esther Kobel, Dining with John: Communal Meals and Identity Formation in the Fourth Gospel and its Historical and Cultural Context (Biblical Interpretation Series 109; Leiden – Boston: Brill 2011). Pp. 375. 176.00. €135,00. ISBN 9789004217782 (Hardback).